131k views
1 vote
Solve for c 9c-7=7c-11

2 Answers

4 votes

Answer:

2

Explanation:

Simplifying

9c + -7 = 7c + -11

Reorder the terms:

-7 + 9c = 7c + -11

Reorder the terms:

-7 + 9c = -11 + 7c

Solving

-7 + 9c = -11 + 7c

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-7c' to each side of the equation.

-7 + 9c + -7c = -11 + 7c + -7c

Combine like terms: 9c + -7c = 2c

-7 + 2c = -11 + 7c + -7c

Combine like terms: 7c + -7c = 0

-7 + 2c = -11 + 0

-7 + 2c = -11

Add '7' to each side of the equation.

-7 + 7 + 2c = -11 + 7

Combine like terms: -7 + 7 = 0

0 + 2c = -11 + 7

2c = -11 + 7

Combine like terms: -11 + 7 = -4

2c = -4

Divide each side by '2'.

c = -2

Simplifying

c = -2

User Prayag Gordy
by
5.6k points
3 votes

Answer:

c = -2

Explanation:


9c-7=7c-11\qquad\text{add 7 to both sides}\\\\9c-7+7=7c-11+7\\\\9c=7c-4\qquad\text{subtract}\ 7c\ \text{from both sides}\\\\9c-7c=7c-7c-4\\\\2c=-4\qquad\text{divide both sides by 2}\\\\(2c)/(2)=(-4)/(2)\\\\c=-2

User Nbrew
by
6.2k points